Hubungan Peran Kelompok Pendukung Ibu Dengan Keberhasilan Pemberian Asi Eksklusif Di Wilayah Kerja Puskesmas Gambirsari Surakarta - Septianingrum, Anisa; , H. Heru Subaris K., S.KM, M.Kes; , Anisa Catur Wijayanti, SKM., M.Epid (2016)
Exclusive breastfeeding is only giving breast milk, when baby was born until six month, without any other food. The aim of exclusive breastfeeding program is to implementation one of MDGS project, for decrease morbidity and mortality from neonatal and babies. The coverage of exclusive breastfeeding in Surakarta (55,7%) is still under national target level (80%). One of the eforts from goverment to increase exclusive breastfeeding is to decided ten steps for succesfully suckle program, among of them is to organization mother supporting group. The aim of this research is to knowing the role in mother supporting group with succesfully of giving exclusive breastfeeding at Puskesmas Gambirsari Surakarta. The method of this research is using crossectional design. There were 88 samples. They were taken by simple random sampling technique. Chi-square and Fisher exact were used as bivariat analysis. The result of bivariat analysis showed that there are relationship between mother decided for suckle with succesfully giving exclusive breastfeeding (p=0,039) and there are not relationship between the role in mother supporting group with mother decided for suckle (p=0,611) and succesfully of giving exclusive breastfeeding (p=0,192).